Media and Social Presumption of Guilt and the Legal Guidance of Innocence (Legal Look and a New Perspective) - Patora, Krystyna (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
The topic of the article are the considerations which regard the obligatory in the penal code presumption of innocence as well as the presumption of guilt, which may arise in the media thereby in the public opinion. Legal solutions in criminal law, press law and international law have been discussed to counteract the creation of a false picture of processes. In addition, judicial decisions have been pointed out, which set the requirements for reliable information on the course of preparatory and court proceedings, as well as special attention paid to spokespersons.